Social media, Islam and ethics: a study of instagram use by students of a public university in Malaysia - Mokhtar, Aida (2018)
According to the literature, Malaysians are the most active users of Instagram in the Asia Pacific in 2016. The popularity of Instagram is comparable to the United States where young adults are heavy users of Snapchat and Instagram in 2018. For the Malaysian Communications and Multimedia Commission (MCMC), the Internet Users Survey 2017 finds 56.1 percent of the Malaysian population using Instagram that makes it the second most popular social networking platform after Facebook overall. Instagram is popular. The social media platform, like other forms of media, can potentially affect the user audience on positive or detrimental levels or both. There appears to be the absence of research studies on Instagram use by university students and Islam in Malaysia. The effects of Instagram are of great concern for Muslim students who pursue university education. The students are expected to focus on their studies and some live a long distance away from their families allowing them to take on a more independent role. Their use of the media is of great concern. Bandura posits through social learning theory that people learn through observation, imitation and modelling. The purpose of the study is to examine Instagram use from a social learning perspective so as to determine its effects on the students of a public university in Malaysia. The students could imitate bad or good behaviour depicted on Instagram. It is important for Muslims to use Instagram ethically as Islam is a way of life. Young Muslims are encouraged to be guided by Islamic ethics and pursue the goal of eternal goodness in the Hereafter. Muslim users need to be concerned about the potentially negative effects of Instagram and use the social media platform with caution.